The lexicon of power in the translations of Life of Cicero by Plutarch (Circe de clásicos y modernos, 2020)
The Parallel Lives of Plutarch sought to depict the character and customs of Greek and Roman statesmen (Alexander 1). Their virtuous actions regarded as beautiful examples of behavior (Aemilius Paulus 1), by means of taking into consideration behavior without virtue (Cimon 2), to shape character and promote action (Pericles 2). Moreover, these bíoi also allow the making of further readings on aspects which concerned the author. One of these aspects were the different forms that power took during the lives of biographees, seen through the eyes of an elite Greek under Roman rule.
Keywords: Plutarch; lexicon; power; translation; Republic